2006
DOI: 10.1177/021849230601400213
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral Axillary Arterial Perfusion in Surgery on Thoracic Aorta

Abstract: Bilateral axillary arterial cannulation for selective cerebral perfusion might minimize cerebral embolic complications during surgery on the ascending aorta and aortic arch. From March 2002 through February 2004, bilateral axillary arterial perfusion was applied in 12 consecutive patients (mean age, 61.3 years). Operative procedures were total arch replacement in 8 patients, hemiarch replacement in 1, and ascending aorta replacement in 3. Antegrade selective cerebral perfusion was established through vascular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(32 citation statements)
references
References 19 publications
0
32
0
Order By: Relevance
“…Even in elective proximal arch surgeries, a 6% rate of paraplegia is encountered, highlighting the need for further measures to reduce this devastating complication, especially in the case of more time demanding extensive aortic repairs 21 . In this context, additional perfusion of LSA seems to be beneficial, particularly in critical vascular conditions, such as concomitant carotid dissections, acute right vertebral artery occlusion, dominant LVA, or inadequate intracranial arterial communications 22–27 . Notably, studies reporting on outcomes after thoracic endovascular aortic repair with overstenting of the LSA have demonstrated an increased risk of left‐hemispheric stroke and permanent paraplegia 28–30 .…”
Section: Resultsmentioning
confidence: 99%
“…Even in elective proximal arch surgeries, a 6% rate of paraplegia is encountered, highlighting the need for further measures to reduce this devastating complication, especially in the case of more time demanding extensive aortic repairs 21 . In this context, additional perfusion of LSA seems to be beneficial, particularly in critical vascular conditions, such as concomitant carotid dissections, acute right vertebral artery occlusion, dominant LVA, or inadequate intracranial arterial communications 22–27 . Notably, studies reporting on outcomes after thoracic endovascular aortic repair with overstenting of the LSA have demonstrated an increased risk of left‐hemispheric stroke and permanent paraplegia 28–30 .…”
Section: Resultsmentioning
confidence: 99%
“…Kazui [24] advocates that in a surgery which requires selective cerebral perfusion time superior to 30 minutes or aortic arch replacement, the bilateral perfusion method is the appropriate choice for neurologic protection. Kuriso et al [19] described the use of bilateral cerebral perfusion through cannulation of both axillary arteries and the insertion of a catheter into left carotid artery, thus imposing a great surgical complexity and manipulation to the procedure. Griepp et al [25] described the use of bilateral cerebral reperfusion through a Dacron tube implantation into the origin block of brachiocephalic vessels which is anastomosed posteriorly to the tube replacing the ascending aorta.…”
Section: Resultsmentioning
confidence: 99%
“…Kazui et al [18] described a technique for bilateral antegrade selective cerebral perfusion through cannulation of the brachiocephalic trunk and the left common carotid artery, using a 15Fr-retrograde perfusion cannula of coronary sinus with a manually-inflatable balloon. Kurisu et al [19] used antegrade selective cerebral perfusion established by vascular grafts anastomosed to the bilateral axillary arteries and a perfusion catheter placed directly into the left carotid artery. Minatoya et al [20] reported the use of antegrade selective cerebral perfusion for brain protection in the reconstruction of the arch using independent perfusion from arch vessels by using quadrifurcated grafts.…”
Section: Introductionmentioning
confidence: 99%
“…Two spring retractors were used to enhance exposure of the operative field. 7) Cardiopulmonary bypass was initiated with bilateral axillary arterial perfusion 8) and bicaval drainage. Adding direct cannulation to both carotid arteries enabled selective cerebral perfusion.…”
Section: Case Reportmentioning
confidence: 99%